2016
DOI: 10.3389/fpsyg.2016.00227
|View full text |Cite
|
Sign up to set email alerts
|

All for One: Contributions of Age, Socioeconomic Factors, Executive Functioning, and Social Cognition to Moral Reasoning in Childhood

Abstract: Moral reasoning (MR) is a socio-cognitive skill essential to appropriate social functioning in childhood, and evolves in quality and complexity during ontogenetic development. Past research suggests that MR is related to age, socioeconomic factors, as well as some social and cognitive skills, such as executive functioning (EF), theory of mind (ToM), empathy, and affect recognition. However, their contributions have been studied in silos rather than comprehensively, with little integration of the relative and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 84 publications
2
33
1
Order By: Relevance
“…Participants completed the SoMoral ( Dooley et al, 2010 ; Beauchamp and Dooley, 2012 ; Beauchamp et al, 2013 ; Vera-Estay et al, 2015 , 2016 ; Chiasson et al, 2017 ). The SoMoral is a self-paced, visual, computer-based task.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants completed the SoMoral ( Dooley et al, 2010 ; Beauchamp and Dooley, 2012 ; Beauchamp et al, 2013 ; Vera-Estay et al, 2015 , 2016 ; Chiasson et al, 2017 ). The SoMoral is a self-paced, visual, computer-based task.…”
Section: Methodsmentioning
confidence: 99%
“…The Socio-Moral Reasoning Aptitude Level Task (SoMoral; Dooley et al, 2010 ; Beauchamp and Dooley, 2012 ; Beauchamp et al, 2013 ; Vera-Estay et al, 2015 , 2016 ; Chiasson et al, 2017 ) is a visual moral reasoning measure that contains moral dilemmas from everyday life situations presented using pictures. It measures three aspects of moral reasoning: understanding, decision-making, and justification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other analyses revealed that the cognitive dimension more robustly associated with child conduct problems and prosociality than did the affective dimension (Dadds et al, 2008). A growing number of studies have since relied upon these GEM cognitive and affective scales (e.g., Dadds, Cauchi, Wimalaweera, Hawes, & Brennan, 2012;Dawel, Palermo, O'Kearney, & McKone, 2015;Decety, Meidenbauer, & Cowell, 2017;Deschamps, Been, & Matthys, 2014;D'Hondt et al, 2017;Kimonis et al, 2016;McDonald et al, 2017;Tsang, Gillespie-Lynch, & Hutman, 2016;Vera-Estay, Seni, Champagne, & Beauchamp, 2016). The original validation article (Dadds et al, 2008) and the first major follow-up article (Dadds et al, 2009) have both already been cited more than 100 times according to the Google Scholar database, with a few dozen citations each since 2016.…”
mentioning
confidence: 99%
“…The Socio-Moral Reasoning Ability Level task (SoMoral) [ 1 , 11 , 42 44 ] addresses some of these methodological limitations. The task consists of visual dilemmas that represent moral conflicts (e.g.…”
Section: Introductionmentioning
confidence: 99%